ANALISIS FAKTOR PENYEBAB CERAI GUGAT DI KECAMATAN PARIAMAN TENGAH TAHUN 2017-2018 (STUDI KASUS PENGADILAN AGAMA PARIAMAN KELAS 1B) - Fairuzy Isma M; afdhal afdhal (JURNAL BUANA, 2020)
This study aims to determine: (1) Factors that cause divorce in Pariaman Tengah District in 2017 and (2) factors that cause divorce in Pariaman Tengah District in 2018. The type of research is descriptive qualitative. The source of the informants in this study was the Young Registrar of Law in the Pariaman Class Court 1B. Data collection techniques are interviews and observation. Data analysis techniques such as data collection, data reduction, data presentation, and verification. The results showed that in 2017 the first factor was continuous disputes and quarreling, one party leaving factor, economic factors, cultural factors, body disability factors, attitude factors, and finally the presence of domestic violence factors. The first factors which cause divorce in 2018 are the factors of continuous disputes and quarrels, factors of leaving a partner, economic factors, factors of domestic violence, cultural factors, attitude factors, disability factors.